2016
DOI: 10.1038/nprot.2016.159
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of mitochondria in mammalian cells through enforced mitophagy

Abstract: Mitochondria are not only the "power-house" of the cell, but are also involved in a multitude of processes that include calcium storage, cell-cycle and cell-death. Traditional means to investigate mitochondrial importance in a given cellular process have centred upon depletion of mitochondrial DNA (mtDNA) through chemical or genetic means. While these methods severely disrupt mitochondrial electron transport chain, mtDNA-depleted cells still maintain mitochondria and many mitochondrial functions. Here, we desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 38 publications
1
48
0
Order By: Relevance
“…S2b , left) and subjected to a short-term CCCP treatment for widespread mitophagy induction. 33 In these cells, mitophagy, indicated by the co-localization of mitochondria with LC3, was clearly observed (Supplementary information, Fig. S2a , right), and mitochondrial proteins or mitochondrial DNA (mtDNA) could be hardly detected (Supplementary information, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S2b , left) and subjected to a short-term CCCP treatment for widespread mitophagy induction. 33 In these cells, mitophagy, indicated by the co-localization of mitochondria with LC3, was clearly observed (Supplementary information, Fig. S2a , right), and mitochondrial proteins or mitochondrial DNA (mtDNA) could be hardly detected (Supplementary information, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ototoxic drugs are a common cause of sensorineural hearing loss, and aminoglycosides are the most commonly used ototoxic drugs. Cochlear HCs are susceptible to aminoglycoside-mediated cytotoxicity and cannot be regenerated once damaged, and thus aminoglycoside ototoxicity is usually associated with permanent sensorineural deafness ( Nadol, 1993 ; Lazarou et al, 2015 ; Correia-Melo et al, 2017 ). Recent studies have reported that HCs in the mouse cochlea have a very limited ability to regenerate during the neonatal period, but this limited spontaneous HC regeneration is not sufficient to restore hearing ability once HCs are destroyed by aminoglycosides, and all regenerative ability is lost a few days after birth ( Li et al, 2016 ; Ni et al, 2016 ; Waqas et al, 2016 ; Lu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria have traditionally been viewed as the powerhouse of the cell due to their central role in metabolism and energy production. More recently, mitochondria have been implicated in other cellular roles including calcium storage, migration, cell death, senescence, and inflammation [19]. Sustaining mitochondria is one of the important functions of astrocyte in CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of mitochondria demonstrated more energy support for astrocytes and neurons. Moreover, mitochondria have been implicated in inflammation, cell death, and senescence [19].…”
Section: Introductionmentioning
confidence: 99%